2020
DOI: 10.1111/hae.14217
|View full text |Cite
|
Sign up to set email alerts
|

An overview of patients with haemophilia A in China: Epidemiology, disease severity and treatment strategies

Abstract: Introduction Haemophilia A (HA) is a rare X chromosome‐linked bleeding disorder resulting in missing or defective clotting factor VIII (FVIII) and causes large disease burden. Aim As a member of World Federation of Hemophilia, China seeks to understand the current epidemiology, disease profile and treatment landscape of patients with HA through the Hemophilia Treatment Center Collaboration Network of China (HTCCNC). Methods The HTCCNC enabled data collection on patients with HA from 166 member hospitals (2007–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…The distribution of disease severity (43% severe, 33% moderate, and 24% mild) is similar to that of mainland China and Taiwan. Notably, the rate of prophylactic factor infusion (34%) among patient with hemophilia in Hong Kong is slightly higher than the estimated rate (16.2%) in a report from mainland China [ 20 ]. The population factor use of 1.83 units of FVIII per capita [ 19 ] is comparable to factor consumption levels in other developed countries in Asia, such as Korea, Japan, and Singapore [ 21 ].…”
Section: Introductionmentioning
confidence: 85%
“…The distribution of disease severity (43% severe, 33% moderate, and 24% mild) is similar to that of mainland China and Taiwan. Notably, the rate of prophylactic factor infusion (34%) among patient with hemophilia in Hong Kong is slightly higher than the estimated rate (16.2%) in a report from mainland China [ 20 ]. The population factor use of 1.83 units of FVIII per capita [ 19 ] is comparable to factor consumption levels in other developed countries in Asia, such as Korea, Japan, and Singapore [ 21 ].…”
Section: Introductionmentioning
confidence: 85%
“…7 In developing countries of the Asia-Pacific region, the disease burden associated with hemophilia A is greater compared with Western countries, with the limited use of prophylaxis being one of the main contributing factors. 8,9 The Asia-Pacific Hemophilia Working Group has developed a Principles of Hemophilia Care document, taking into account variability in regional health care systems and the socioeconomic and cultural diversities, in an effort to drive forward hemophilia care in the region. 10 There remains, however, a high unmet need in reducing disease burden for people with hemophilia A in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%
“…40 Previous studies conducted in China indicated that, late initiation of prophylaxis, coagulation factor deficiency and poor compliance may explain the limited impact of prophylaxis on HRQoL in PwH. 3,5 This study had several limitations. First, the cross-sectional survey was suitable for determining associations but not for determining…”
Section: Discussionmentioning
confidence: 93%
“…Another reason might be the differences in the level of haemophilia management. A previous study suggested that the prophylaxis of haemophilia in China lagged behind developed countries such as the United Kingdom and the United States, 5 which might have an impact on the HRQoL of patients in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation